Gustos, preferencias y posicionamiento de los productos OMNILIFE en el cantón Quevedo 2010 y Plan de comunicación para el período 2011. - Garcés Mora, Marlene Rosario (2011)
The research project is organized chapters, to determine "preferences and Omnilife Product Positioning "and performs a alternative proposal to increase demand in Quevedo market, the first part offers a introduction and discusses the definition of the problem is the first step and most important, the second step is definition of objectives allowing design project aims to research, ie statement of study directed toward the solution problem. Within the framework of the project raised the general hypothesis "Market Research for Omnilife on their tastes and preferences customers will increase the positioning Business in the City of Quevedo "coming up to determine that the total survey, 33.63% did not consume nutritional products; on the benefits of 34.52% Omnilife the product does not answer, is also I sense that the population tends to consume Biocros product by 20.36% and other products have a much lower priority. The chapter of theoretical framework was to describe fully the variables of the study, all records concerning to the research and listening to the sources literature, documentaries that were related to research. It also describes and details the type of research: descriptive - history and the methods applied field deductive, inductive, the survey technique and instrument through a series of questions, in As the chapter on the analysis result shows field work from a practical standpoint, too includes the conclusions and recommendations of the process research it was obtained after analyzing using statistical techniques that have allowed sufficient information about the proposal Omnilife alternative for the Company in the City of Quevedo.